Women's experiences of seeking healthcare for abdominal pain in Ireland: a qualitative study - Eibhlín B. Windrim; Brian E. McGuire; Hannah Durand (BMC, 2024)
Abstract Background Evidence suggests that women's abdominal pain is more likely to be minimised or dismissed by healthcare professionals than men's. This can have a detrimental impact on health-related outcomes as well as quality of life. The aim of this study was to explore women's experiences of seeking healthcare for abdominal pain in Ireland. Method A qualitative design and opportunity sampling approach were employed in this study. Fourteen women living in Ireland with experience of seeking healthcare for abdominal pain took part in one-to-one semi-structured interviews via video-conferencing software. Data were analysed using reflexive thematic analysis. Results Four themes were constructed from the data: [1] "Just Get on with It" - Normalisation and Invalidation; [2] "Bad Enough"? Costs of (Not) Seeking Help; [3] "Fight Your Case," Fight for Care; and [4] "Out of the Loop" - Systemic Barriers to Care. Perceived invalidation of pain by healthcare professionals was common, as was internalised normalisation of pain. This created challenges when negotiating pain management solutions. Despite functional interference, participants felt their pain needed to reach an extreme level of severity before seeking help. Costs of private healthcare were implicated in delayed help-seeking. Participants felt the onus was on them to fight for care. Social support and information-seeking facilitated participants in this fight while systemic issues were identified as barriers to adequate care. Despite their frustrations, participants expressed empathy for healthcare professionals operating in a flawed system. Conclusions Participants described mostly negative experiences of seeking healthcare for abdominal pain, characterised by dismissal of symptoms and internalisation of normative views of women's pain as less worthy of care. These experiences reinforced participants' views that self-advocacy is essential to access care for their pain. There are systemic issues at play within the Irish healthcare system that limit women's ability to access abdominal pain management support. Education and training for healthcare professionals on the Gender Pain Gap and its implications for patient care, as well as clear referral pathways for women presenting with abdominal pain, may help to ensure more equitable healthcare delivery for individuals with abdominal pain in Ireland.